Impact of reticulin stain in clinical outcome of Immune Thrombocytopenic Purpura (ITP): a pathologist perspective - Rafael Guimarães Kanda; Lígia Niero-Melo; Maria Aparecida Custódio Domingues; Cristiano Claudino Oliveira (BMC, 2022)
Abstract Background This study evaluated histopathological characteristics of bone marrow (BM) of patients with immune thrombocytopenic purpura (ITP) and sought to find possible associations among them and clinical aspects. Method A retrospective study was carried out with 120 patients using BM clot and BM biopsy samples, including morphological (cytological and histological) re-evaluation, reticulin and hemosiderin analysis, and clinical outcome review of medical records. Immunohistochemistry (CD34 and CD117) was applied in a group of patients with increased reticulin, with the objective of exclusion Myelodysplastic syndrome cases Results Megakaryocytic hyperplasia was observed in 109 (90.8%) patients and increased reticulin was diagnosed in nine patients, five of them with a clinically unfavorable outcome (p = 0.042). The increase in reticulin graduation was associated with a higher risk of an unfavorable outcome. Conclusion Increased reticulin degree in BM of patients with ITP is associated with an unfavorable outcome in this study. It is rarely explored in the literature and may provide information that contributes to understanding the patient's outcomes.